f-Statistical convergence on topological modules - Francisco Javier García-Pacheco; Ramazan Kama (Electronic Research Archive, 2022)
The classical notion of statistical convergence has recently been transported to the scope of real normed spaces by means of the $ f $-statistical convergence for $ f $ a modulus function. Here, we go several steps further and extend the $ f $-statistical convergence to the scope of uniform spaces, obtaining particular cases of $ f $-statistical convergence on pseudometric spaces and topological modules.